Primary resonance of a beam-rigid body microgyroscope. (December 2015) - Lajimi, S.A.M.; Heppler, G.R.; Abdel-Rahman, E.M.
Abstract: We present the non-linear dynamical features of a beam-rigid-body microgyroscope operating under the electrostatic force. A comprehensive system of discretized governing equations is solved using the method of multiple scales and the shooting method. For an amplitude-modulation gyro, the effects of the quality factor, AC voltage, and the rotation rate on the response are investigated and the fold-bifurcation points are identified. A frequency-modulation gyro is examined and in addition to the bifurcation points, the entrainment region is identified. The effects of a positive and a negative internal detuning parameter on the frequency-response of a frequency-modulation gyro are investigated.